Unnalli Melo's Theology and Peace Study on the Concept and Reality of Peace in Toraja Culture - Rannu Sanderan; Daniel Ronda; Robi Panggarra; Andrew Buchanan (Jurnal Jaffray, 2022)
This essay aims to examine the reality of peace in Toraja. In the last ten years have been surrounded by conflicts in neighbouring areas. The type of research is a qualitative approach with ethnography methods. This research aims to look for virtue in Toraja human nature, the environment, oneself, and God or all at once. This research seeks to explain, evaluate, and study the portrait of the encounter of the peaceful reality of Toraja culture with the most significant importance of peace in the Bible. It can be concluded that the unique moral qualities in the minds of the Torajan people can be interpreted as the interconnectivity of values in the cosmic integrity of the Toraja people. The monumental work of translating the Bible into Sura' Madatu became the shaper of a new character. The expression to love the enemy is one of the ultimate values in the teachings of Jesus and shocks many people.